Recurrent Peptic Ulcer due to Carcinoid Tumour of Jejunum - Bhattacharyya, Parimal (Springer-Verlag, 2011)
Carcinoid Tumours are classified as Neuro-endocrine tumours. Commonly known ulcerogenic neuro-endocrine tumour is Gastrinoma of the Pancreas and Duodenum.It secretes hormone Gastrin which causes hyperplasia of the gastric parietal cells with excessive secretion of hydrochloric acid resulting in multiple ulcerations in the stomach, duodenum and upper jejunum. Carcinoid tumours is not known to cause peptic ulceration.